Pengaruh Kualitas Jasa Layanan Terminal Pelabuhan Terhadap Kepuasan Penumpang Kapal Feri di Pelabuhan Penyeberangan Baubau - Yusuf Jaya Saputra; Sayyid Ahmad; Maudhy Satyadharma (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
The Baubau Crossing Port as one of the ports managed by the Provincial Government of Southeast Sulawesi plays a vital and important role in encouraging the movement of people and goods in and out of Baubau City. This research was conducted to analyze the influence of the quality of port terminal services on the satisfaction of ferry passengers at the Baubau Crossing Port. The sample of this research is 60 passengers with accidental sampling system. The results of the study concluded that there was a positive and significant influence between the quality of port terminal services and the level of satisfaction of ferry passengers at the Baubau Crossing Port.